2014
DOI: 10.1021/ol500706z
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of the First Water-Soluble Hemicryptophane Host: Selective Recognition of Choline in Aqueous Medium

Abstract: The first water-soluble hemicryptophane cage compound, 4, was synthesized in seven steps from commercially available products, and its complexation properties were studied. NMR and ITC experiments indicate that 4 is an efficient receptor for choline in water (ΔG° = -5.2 kcal mol(-1)). High substrate selectivity was achieved since no complexation was observed for its closely related substrates: glycine betaine and betaine aldehyde. Density functional theory calculations were performed to analyze the interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 46 publications
2
22
0
Order By: Relevance
“…These results can be compared to previous solution-phase results from three different perspectives. First, gas-phase results obtained for hemicryptophane 2 with choline and betaine guest molecules are consistent with those observed in solution [22]. Employing a very similar hemicryptophane cage that is water soluble, a selective recognition towards choline versus betaine was observed in solution [22].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…These results can be compared to previous solution-phase results from three different perspectives. First, gas-phase results obtained for hemicryptophane 2 with choline and betaine guest molecules are consistent with those observed in solution [22]. Employing a very similar hemicryptophane cage that is water soluble, a selective recognition towards choline versus betaine was observed in solution [22].…”
Section: Discussionsupporting
confidence: 76%
“…The structure of a hemicryptophane molecule differs from a cryptophane cage in that one of the CTV caps is replaced with a C3-symmetrical organic group [20]. Hemicryptophanes have been employed for selective inclusion of choline [22], choline phosphate [23] or primary alkylammonium ions [24]. Moreover, hemicryptophanes have been used for enantioselective recognition [25,26] as well as ion-pair recognition [27] and studies pertaining to potential catalytic activity [28] have also been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Gas‐phase investigation of H‐G systems is of great importance in providing information regarding their intrinsic structural and binding properties. Solution‐phase studies have shown that hemicryptophane cages of various types can exhibit binding selectivity toward suitable guests, resulting in encapsulation of the guest . However, the degree of encapsulation and the strength of H‐G binding in solution may be influenced by solvation and counter ion effects.…”
Section: Introductionmentioning
confidence: 99%
“…Solution-phase studies have shown that hemicryptophane cages of various types can exhibit binding selectivity toward suitable guests, resulting in encapsulation of the guest. 7,8,20,21,[26][27][28] However, the degree of encapsulation and the strength of H-G binding in solution may be influenced by solvation and counter ion effects. Gas phase studies, on the other hand, can provide a more direct means to probe intrinsic interactions between host and guest without the additional encumbrance of solvent molecules.…”
Section: Introductionmentioning
confidence: 99%
“…We thus focused on tren–hemicryptophanes containing the C 3 ‐symmetric tris(2‐aminoethyl)amine (tren) ligand, which exhibited substrate‐, diastereo‐, and enantioselective recognition properties toward neurotransmitters and carbohydrates ,. Moreover, encaged azatrane structures can be formed when a metal or heteroelement is introduced into the tren unit.…”
Section: Introductionmentioning
confidence: 99%